Odpowiedź:
[tex]\huge\boxed{P(A)=\dfrac{1291}{1296}}[/tex]
Szczegółowe wyjaśnienie:
Wiemy, że:
[tex]P(A)=1-P'(A)[/tex]
[tex]P'(A)[/tex] - zdarzenie przeciwne
Obliczmy prawdopodobieństwo zdarzenia przeciwnego.
[tex]\Omega=\bigg\{(a,\ b,\ c,\ d):\ a,b,c,d\in\{1,\ 2,\ 3,\ 4,\ 5,\ 6\}\bigg\}\\\\|\Omega|=6^4=1296[/tex]
[tex]A'=\bigg\{(a,\ b,\ c,\ d):a,b,c,d\in\{1,\ 2,\ 3,\ 5,\ 6\}\ \wedge\ a+b+c+d<6\bigg\}\\\\A'=\{(1,1,1,1);\ (1,1,1,2);\ (1,1,2,1);\ (1,2,1,1);\ (2,1,1,1)\}\\\\|A'|=5\\\\P(A')=\dfrac{5}{1296}[/tex]
[tex]P(A)=1-\dfrac{5}{1296}=\dfrac{1296}{1296}-\dfrac{5}{1296}=\dfrac{1291}{1296}[/tex]